The use of socrative as a pedagogical alternative for the performance of team-based learning (TBL) in the classroom (Research, Society and Development, 2020)
Aware of the constant insertion of electronic devices among students in the classroom. The objective of this work was to propose the use of the socrative application as a pedagogical alternative for the realization of Team-Based Learning (TBL) in the classroom. It is an exploratory study with a quali-quantitative approach. For the development of this research, a classroom activity was carried out divided into stages with 13 students from the pharmacy course. Initially the study material was made available and a conference was held, at the second moment the TBL was applied by the socrative application and later a questionnaire was made available through Google Forms in order to evaluate the methodology used. After the activity, it was observed that the methodology used had a satisfactory result, since the performance of the students improved considerably in terms of autonomy, decision-making capacity and teamwork, obtaining an acceptance rate of 93%. It was concluded that the use of this application can help teachers in the elaboration and realization of TBL, and in the development of other activities in class, since it has several advantages, besides being free.